Microwave-induced self-organization in mineral systems. V. FeCl3 colloid (800 W; 2.45 GHz; 30 sec.) - Oleg V Gradov; Margaret A Gradova (PANGAEA, 2019)
Microwave-induced self-organization in FeCl3 colloids under high irradiation power (800 W) is strongly dependent on the layer thickness of the precursor (saturated ferric chloride solution) and results in less diversity of membraneous structure morphologies because of the too fast water evaporation preventing hydrolytic polycondensation and favoring simple crystallization of the mineral phases.